The Cd(II)-binding abilities of recombinant Quercus suber metallothionein: bridging the gap between phytochelatins and metallothioneins. (Journal of biological inorganic chemistry : JBIC : a publication of the Society of Biological Inorganic Chemistry, 2007)
In this work, we have analyzed both at stoichiometric and at conformational level the Cd(II)-binding features of a type 2 plant metallothionein (MT) (the cork oak, Quercus suber, QsMT). To this end four peptides, the wild-type QsMT and three constructs previously engineered to characterize its Zn(II)- and Cu(I)-binding behaviour, were heterologously produced in Escherichia coli cultures supplemented with Cd(II), and the corresponding complexes were purified up to homogeneity. The Cd(II)-binding ability of these recombinant peptides was determined through the chemical, spectroscopic and spectrometric characterization of the recovered clusters. Recombinant synthesis of the four QsMT peptides in cadmium-rich media rendered complexes with a higher metal content than those obtained from zinc-supplemented cultures and, consequently, the recovered Cd(II) species are nonisostructural to those of Zn(II). Also of interest is the fact that three out of the four peptides yielded recombinant preparations that included S(2-)-containing Cd(II) complexes as major species. Subsequently, the in vitro Zn(II)/Cd(II) replacement reactions were studied, as well as the in vitro acid denaturation and S(2-) renaturation reactions. Finally, the capacity of the four peptides for preventing cadmium deleterious effects in yeast cells was tested through complementation assays. Consideration of all the results enables us to suggest a hairpin folding model for this typical type 2 plant Cd(II)-MT complex, as well as a nonnegligible role of the spacer in the detoxification function of QsMT towards cadmium.

The Cd(II)-binding abilities of recombinant Quercus suber metallothionein: bridging the gap between phytochelatins and metallothioneins. - Domenech, Jordi; Orihuela, Ruben; Mir, Gisela; Molinas, Marisa; Atrian, Silvia; Capdevila, Merce (Journal of biological inorganic chemistry : JBIC : a publication of the Society of Biological Inorganic Chemistry, 2007)
In this work, we have analyzed both at stoichiometric and at conformational level the Cd(II)-binding features of a type 2 plant metallothionein (MT) (the cork oak, Quercus suber, QsMT). To this end four peptides, the wild-type QsMT and three constructs previously engineered to characterize its Zn(II)- and Cu(I)-binding behaviour, were heterologously produced in Escherichia coli cultures supplemented with Cd(II), and the corresponding complexes were purified up to homogeneity. The Cd(II)-binding ability of these recombinant peptides was determined through the chemical, spectroscopic and spectrometric characterization of the recovered clusters. Recombinant synthesis of the four QsMT peptides in cadmium-rich media rendered complexes with a higher metal content than those obtained from zinc-supplemented cultures and, consequently, the recovered Cd(II) species are nonisostructural to those of Zn(II). Also of interest is the fact that three out of the four peptides yielded recombinant preparations that included S(2-)-containing Cd(II) complexes as major species. Subsequently, the in vitro Zn(II)/Cd(II) replacement reactions were studied, as well as the in vitro acid denaturation and S(2-) renaturation reactions. Finally, the capacity of the four peptides for preventing cadmium deleterious effects in yeast cells was tested through complementation assays. Consideration of all the results enables us to suggest a hairpin folding model for this typical type 2 plant Cd(II)-MT complex, as well as a nonnegligible role of the spacer in the detoxification function of QsMT towards cadmium.
The following values have no corresponding Zotero field: accession-num: 17503092
Keywords: cadmium; Cadmium: chemistry; Cadmium–His binding; Drug; Glutathione; Metabolic Detoxication; metallothionein; Metallothionein: chemistry; Metallothionein: metabolism; Phytochelatins; Plant metallothionein; Plant Proteins; Plant Proteins: chemistry; Plant Proteins: metabolism; Protein Binding; Protein Conformation; Quercus; Recombinant Proteins; Sulfide ligands; yeast complementation

Plant metallothionein domains: functional insight into physiological metal binding and protein folding (BIOCHIMIE, 2006)
Plant metallothioneins (MTs) differ from animal MTs by a peculiar sequence organization consisting of two short cysteine-rich terminal domains linked by a long cysteine-devoid spacer. The role of the plant NIT domains in the protein structure and functionality is largely unknown. Here, we investigate the separate domain contribution to the in vivo binding of Zn and Cu and to confer metal tolerance to CUP1-null yeast cells of a plant type 2 NIT (QsMT). For this purpose, we obtained three recombinant peptides that, respectively, correspond to the single N-terminal (N25) and C-terminal (C18) cysteine-rich domains of QsMT, and a chimera in which the spacer is replaced with a four-glycine bridge (N25-C18). The metal-peptide preparations recovered from Zn- or Cu-enriched cultures were characterized by ESI-MS, ICP-OES and CD and UV-vis spectroscopy and data compared to full length QsMT. Results are consistent with QsMT giving rise to homometallic Zn- or Cu-MT complexes according to a hairpin model in which the two Cys-rich domains interact to form a cluster. In this model the spacer region does not contribute to the metal coordination. However, our data from Zn-QsMT (but not from Cu-QsMT) support a fold of the spacer involving some interaction with the metal core. On the other hand, results from functional complementation assays in endogenous MT-defective yeast cells suggest that the spacer region may play a role in Cu-QsMT stability or subcellular localization. As a whole, our results provide the first insight into the structure/function relationship of plant MTs using the analysis of the separate domain abilities to bind physiological metals. (c) 2005 Elsevier SAS. All rights reserved.

Plant metallothionein domains: functional insight into physiological metal binding and protein folding - Domenech, Jordi; Mir, Gisela; Huguet, Gemma; Capdevila, Merce; Molinas, Marisa; Atrian, Silvia (BIOCHIMIE, 2006)
Plant metallothioneins (MTs) differ from animal MTs by a peculiar sequence organization consisting of two short cysteine-rich terminal domains linked by a long cysteine-devoid spacer. The role of the plant NIT domains in the protein structure and functionality is largely unknown. Here, we investigate the separate domain contribution to the in vivo binding of Zn and Cu and to confer metal tolerance to CUP1-null yeast cells of a plant type 2 NIT (QsMT). For this purpose, we obtained three recombinant peptides that, respectively, correspond to the single N-terminal (N25) and C-terminal (C18) cysteine-rich domains of QsMT, and a chimera in which the spacer is replaced with a four-glycine bridge (N25-C18). The metal-peptide preparations recovered from Zn- or Cu-enriched cultures were characterized by ESI-MS, ICP-OES and CD and UV-vis spectroscopy and data compared to full length QsMT. Results are consistent with QsMT giving rise to homometallic Zn- or Cu-MT complexes according to a hairpin model in which the two Cys-rich domains interact to form a cluster. In this model the spacer region does not contribute to the metal coordination. However, our data from Zn-QsMT (but not from Cu-QsMT) support a fold of the spacer involving some interaction with the metal core. On the other hand, results from functional complementation assays in endogenous MT-defective yeast cells suggest that the spacer region may play a role in Cu-QsMT stability or subcellular localization. As a whole, our results provide the first insight into the structure/function relationship of plant MTs using the analysis of the separate domain abilities to bind physiological metals. (c) 2005 Elsevier SAS. All rights reserved.
The following values have no corresponding Zotero field: pub-location: 23 RUE LINOIS, 75724 PARIS, FRANCE publisher: ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER
Keywords: Cu-aggregates; metallothionein; MT dimers; Quercus suber; separate Cys-rich domains; spacer region; yeast complementation; Zn-aggregates